Technology flows across firms and nations: an assessment of the biotechnology industry. (1st January 2001) - Osegowitsch, Thomas; Madhok, Anoop
This paper seeks to extend our understanding of the dynamics of international diffusion of technology across firms and nations. This involves both geographical and organisational form considerations. The biotechnology industry is utilised as a vehicle both to ground and contextualise the theoretical arguments as well as to explore the relative utility of two prominent theoretical perspectives, one emphasising transaction costs and the other emphasising firm capabilities. An examination of the empirical profile appears to support the dynamic capabilities perspective.